1995
DOI: 10.1113/jphysiol.1995.sp020825
|View full text |Cite
|
Sign up to set email alerts
|

Different types of ganglion cell in the cardiac plexus of guinea‐pigs.

Abstract: 1. Intracellular recordings were made from the parasympathetic ganglion cells that lie in the epicardium of the left atrium of guinea-pig heart near the interatrial septum. 2. Three distinct types of neurone were identified on the basis of their electrophysiological properties. In one group of neurones, S cells, somatic action potentials were followed by brief after-hyperpolarizations. In the other two sets of neurones, somatic action potentials were followed by prolonged after-hyperpolarizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 38 publications
9
115
0
1
Order By: Relevance
“…The mean AHP amplitude was -12.6±0.5 mV (n=28) and reversed at approximately -90 mV, close to the K+ equilibrium potential. The duration of the AHP was highly variable ranging from approximately 50 to 250 ms, reflecting the heterogeneity of the intracardiac ganglion neuron population [2,13,40]. Apamin (1 μM, n=4), iberiotoxin (100 nM, n=6) and ChTX (100 nM, n=6) had no significant effects on the amplitude or duration of the action potential.…”
Section: Bk Channel Contribution To the Action Potential And Ahpmentioning
confidence: 99%
“…The mean AHP amplitude was -12.6±0.5 mV (n=28) and reversed at approximately -90 mV, close to the K+ equilibrium potential. The duration of the AHP was highly variable ranging from approximately 50 to 250 ms, reflecting the heterogeneity of the intracardiac ganglion neuron population [2,13,40]. Apamin (1 μM, n=4), iberiotoxin (100 nM, n=6) and ChTX (100 nM, n=6) had no significant effects on the amplitude or duration of the action potential.…”
Section: Bk Channel Contribution To the Action Potential And Ahpmentioning
confidence: 99%
“…Individual neurons were used for an experiment if the membrane potential was Ϫ40 mV or below and they produced action potentials with an overshoot of at least 20 mV. The neurons were identified as parasympathetic postganglionic neurons by their morphology (ϳ30 m in diameter) and their basic electrical properties relative to previous studies (6,7,16).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the authors demonstrated the presence of three cell subpopulations varying in neurochemical properties. Edwards et al [15], on the other hand, differentiated three neuron types in the cardiac ganglia of guinea pigs, varying in electrophysiological properties. The first type are the so-called S-cells, in which action potential is caused by short hyperpolarisation, while in types 2 and 3, the potential is created due to prolonged hyperpolarisation.…”
Section: Morphology Of Cardiac Gangliamentioning
confidence: 99%